Prospective Associations of Tea Consumption With Risk of Cognitive Decline in the Elderly: A 1-Year Follow-Up Study in China - Li, Wei; Yue, Ling; Xiao, Shifu (Frontiers in Nutrition, 2022)
Abstract Background Previous studies show that the consumption of tea is associated with several beneficial outcomes for brain health, but there is little data among the elderly in China. Objective The objective was to explore the longitudinal relationship between tea consumption and the risk of cognitive decline. Methods The current data was obtained from the China Longitudinal Aging Study (CLAS), and a total of 3246 residents aged 60 years and above were recruited in this study. Some of them (N=111) underwent a standard T1-weighted magnetic resonance imaging (MRI), from which the volumes of the corpus callosum (CC) and hippocampus were calculated, and detailed tea consumption information was obtained through a standardized questionnaire at baseline. The cognitive diagnosis of each participant was made by attending psychiatrists at baseline and follow-up. Their overall cognitive function was assessed by the Montreal Cognitive Assessment (MoCA), while their associative learning ability was assessed by an associative learning test (ALT). Finally, 1545 elderly with normal cognitive function completed the baseline and follow-up assessment and were included in the final study. Results After controlling gender, education, smoking, take exercise and hobbies, we found that the elderly with tea consumption habits had a lower incidence rate of cognitive decline (p=0.002, OR=0.604, 95%CI:0.437~0.836) and tea consumption was negatively correlated with the change scores of MoCA (r=-0.056, p=0.029). What’s more, the CC_posterior volume of tea drinkers was significantly smaller than that of non-tea drinkers, while the baseline ALT score of tea drinkers was significantly higher than that of non-tea drinkers. The results of correlation analysis showed that the CC_posterior volume was significantly correlated with ALT change score (r=-0.319, p=0.010). Conclusions The habit of tea consumption is associated with less incidence of cognitive impairment among the Chinese elderly, and it may prevent a decline in memory and associative learning by affecting the volume of the posterior corpus callosum. Keywords Tea, cognition, elderly, longitudinal study, corpus callosum